Prospective Comparison of Moderate Conscious Sedation and Anesthesia Assistance for the Performance of Endoscopic Retrograde Cholangiopancreatography (ERCP). (14th April 2021) - Akhter, Ahmed; Patel, Ravi; Nelsen, Eric; Benson, Mark E.; Gopal, Deepak V.; Soni, Anurag; Pfau, Patrick
Abstract : Objectives . Recent trends have favored the use of anesthesia personnel more frequently for advanced endoscopic procedures. We hypothesize a selective sedation approach based on patient and procedural factors using either moderate conscious sedation (MCS) or general anesthesia (GA) will result in similar outcomes and safety with significant cost savings. Methods . A 12-month prospective study of all adult endoscopic retrograde cholangiopancreatography (ERCPs) performed at a tertiary medical center was enrolled. Technical success, cannulation rates, procedural related complications, procedure time, and cost were compared between MCS and GA. Results . A total of 876 ERCPs were included in the study with 74% performed with MCS versus 26% with GA. The intended intervention was completed successfully in 95% of cases with MCS versus 96% cases with GA (p  = 0.59). Cannulation success rates with MCS were 97.5 versus 97.8% with GA (p  = 0.81). Overall, adverse event rates were similar in both groups (MCS: 6.6% vs. GA: 9.2%, p  = 0.21). Mean procedure time was less for MCS versus GA, 18.3 and 26 minutes, respectively (p  < 0.0001). Selective use of MCS vs. universal sedation with GA resulted in estimated savings of $8, 190 per case and $4, 735, 202 per annum. Conclusions . Preselection of ERCP sedation of moderate conscious sedation versus general anesthesia based upon patient risk factors and planned therapeutic intervention allows for the majority of ERCPs to be completed with MCS with similar rates of technical success and improvement in resource utilization and cost savings compared to performing ERCPs universally with anesthesia assistance.